2018
DOI: 10.1016/j.compchemeng.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate model generation using self-optimizing variables

Abstract: This paper presents the application of self-optimizing concepts for more efficient generation of steady-state surrogate models. Surrogate model generation generally has problems with a large number of independent variables resulting in a large sampling space. If the surrogate model is to be used for optimization, utilizing self-optimizing variables allows to map a close-to-optimal response surface, which reduces the model complexity. In particular, the mapped surface becomes much "flatter", allowing for a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Mathematical models can be classified into statistical (empirical or black-box) and mechanistic (theoretical, first-principles or white box) models. Statistical methods use techniques such as regression and optimization [179], kriging [180], self-optimizing control [181], and neural networks to derive a set of simple mathematical relations from input and output data [182]. Mechanistic models, on the other hand, employ fundamental discipline-specific theories such as fluid mechanics, thermodynamics, economics, mass and energy balances, etc.…”
Section: Categorization According To Modeling Approachmentioning
confidence: 99%
“…Mathematical models can be classified into statistical (empirical or black-box) and mechanistic (theoretical, first-principles or white box) models. Statistical methods use techniques such as regression and optimization [179], kriging [180], self-optimizing control [181], and neural networks to derive a set of simple mathematical relations from input and output data [182]. Mechanistic models, on the other hand, employ fundamental discipline-specific theories such as fluid mechanics, thermodynamics, economics, mass and energy balances, etc.…”
Section: Categorization According To Modeling Approachmentioning
confidence: 99%
“…Additionally, there is also a substantial effort to explore other common basis functions in surrogate modeling for process-system application including Kriging or Gaussian process models, 2,6 artificial neural networks, 7,8 and splines. 9,10 Another important factor for the performance of surrogate model generation is the design-of-experiment (DoE) method used for the sampling. Garud et al provided a detailed overview of DoE methods.…”
mentioning
confidence: 99%
“…Straus and Skogestad further showed that sampling with standard box constraints on inlet stream and manipulated variables for an ammonia reactor may result in sampling in undesired regions, that is, sampling in regions where the reactor is extinct or shows limit-cycle behavior. 10 Introducing constraints on the manipulated variables (e.g., split ratios or compressor duties) and internal variables based on concepts from process control can avoid sampling in undesired regions.…”
mentioning
confidence: 99%